Theorizing Beauty Regimes: Indonesian Women Performing their Gender Ideology and Resistance through Makeup - Suzie Handajani (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2022)
This article is about how Indonesian women talk about their beauty practices. They are aware how their beauty routines are often seen as banal and shallow but simultaneously essential to their gendered beings. However, this article argues that women are able to subvert the deprecating narratives of their beauty regimes into empowering ones while maintaining the same practices. Through their practices, they seem to conform to the beauty requirement in society. However, through their discourse, they present their beauty regimes with perspectives that put their free will and agency at the centre of their beauty regimes. The research used a sample of twenty-two Indonesian women aged from the mid-twenties to mid-sixties, to ask about beauty routines. Their answers are analyzed by using feminist discourse analysis to seek possibilities of subversion and empowerment. Another theoretical approach used in this research is the politics of everyday lives. The problematization of everyday practices allows for the deconstruction of ideology that perpetuates gendered norms of beauty. This research is significant because it provides a blueprint for further research on gender politics in the 21st century that focuses on everyday practices.